EVALUATION OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE OF PT SOLUSI BANGUN INDONESIA TBK CILACAP PLANT BEFORE AND AFTER THE NAME CHANGE - Anggraeni, Dian (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
This study evaluates CSR disclosure through the dimensions of implementation and reporting using the GRI G4 framework. The results of the study showed that (1) CSR implementation of Solusi Bangun Indonesia Tbk (SBI) Cilacap Plant of 2017 was said to be good through various programs and approaches, as proven by a Community Satisfaction Index of 84.2%; (2) CSR implementation compliance of SBI Cilacap was high because under conditions of poor financial conditions of 2018, the CSR program continued to be implemented in accordance with the rules of law. SBI Cilacap has complied with Law Number 40 of 2007 and Government Regulation Number 47 of 2012; (3) CSR implementation of SBI Cilacap, in terms of ISO 26000, was appropriate; (4) the level of sustainability reports disclosure of Holcim Indonesia of 2017, based on the GRI G4 framework as a whole reached 38%, environmental categories disclosure reached 62%, while economic and social disclosures only reached 22% and 25%. After the name changed as Solusi Bangun Indonesia of 2019, the level of sustainability reports disclosure of 2019, based on the GRI G4 framework as a whole reached 41%, environmental categories disclosure reached 62%, while economic 33% and social disclosures reached 27%. One of the focuses of this research was to evaluate the CSR implementation in a comprehensive manner through the dimensions of implementation and reporting before and after the name change. No previous studies have examined both of them simultaneously.